Productive performance of sheep under intensification program using a twice yearly lambing schedule - I. Gede Putu (Indonesian Center for Animal Research and Development (ICARD), 1995)
A total of 350, three to four year old Daldale ewes were allocated into two treatment groups balanced for age and liveweight. Group TY was joined twice yearly (April-May and September-October) and group OY was joined once yearly (April-May). Three percent of fertile rams fitted with ewe marking crayons and harnesses were used in each group during the six weeks joining period. The productive performance were recorded during three years period. The average raddling rate, lambing rate and number of lambs born per ewe in the TY group were signicantly higher than those of the OY group (P<0.05). However, birth weight, weaning weight and pre-weaning growth rate of the lambs born from the TY group were significantly lighter than those of the OY group (P<0.05). There was no significant difference on wool production between the TY and OY groups (P>0.05). Total weaning weight of lambs horn from both the TY and OY groups for the first, second and third year of research were 2.29 vs 2.49 tons, 2.50 vs 2.63 tons and 1.43 vs 2.34 tons, respectively. It was concluded that the Daldale ewes showed a high proportion of oestrual activity in all year round indicating their suitability for the use in the intensification of sheep husbandry. However, the twice yearly lambing program is still need further research particlularly in selecting breed and other supporting factors.